The CSR of Tobacco Industries: The Concept And Its Implementation - Nanik Trihastuti (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Cigarettes are the products made from tobacco which contains nicotine and tar that has harmful effectswhen they are consumed. Nicotine is identified as an addictive substance while tar contains toxic andcarcinogenic substance. Furthermore, since the harmful effects of the manufactured products, cigarettecompanies should have a responsibility to protect the consumers and their environment, so that they arefreed from the effects. Various companies’ activities which are considered as a company socialresponsibility, such as sponsoring sport events and arts, are actually a massive promotion attempt andeven green camouflage which improve the credibility of the companies as the ones which are notmanufacturing harmful products. Based on the fact, the concept of cigarette company social responsibilityneeds to be reconsidered by differentiating it with other company social responsibilities which havedifferent harmful implications from meanings and realizations.